Intermolecular Characterization of Chitosan from the Exoskeleton of Windu Prawn (Penaeus monodon) and Mangrove Crab (Scylla sp.) - Rini Anggi Arista; Dian Nugraheni; Eka Nurul Qomaliyah; Yayuk Mulyati; Jibril Maulana; Kadek Risa Rivana Dewi; Shahira Qistan A'yuni (Indonesian Journal of Chemical Research, 2026)
Chitosan (C6H11NO4)n is a chitin-derived polymer that has good biocompatibility, biodegradability, and bioabsorbability properties. This compound can be obtained from exoskeleton waste such as mangrove crabs and Windu prawn. This study aims to evaluate the comparison of chitosan levels based on the degree of deacetylation (%DD) from the waste shell, head, and leg of Windu prawn and mangrove crab shell waste obtained from the coastal area of Pasuruan, East Java. The extraction method was carried out through the stages of deproteinization, demineralization, and deacetylation using an alkaline solution, and then the characterization of molecular structure and %DD was carried out using an FTIR spectrophotometer. The results showed that chitosan from Windu prawn shell had the highest %DD of 73.0%, while mangrove crab shell and prawn head and leg showed lower values of 55.3% and 63.9%. This difference in %DD value indicates a variation in the success rate of deacetylation due to differences in biomaterial composition. The results of SEM testing showed that the use of the type of material in the manufacture of chitosan would affect the results of the surface morphology produced, where the Windu prawn shell produced the flattest surface.